If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6m = 42 Solving -6m = 42 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Divide each side by '-6'. m = -7 Simplifying m = -7
| 5x(2x+7)=2 | | 14x-8=34 | | 6-y/(-1)=0 | | 11-(3v+5)=3v-6 | | .15x=23 | | 3w+6-w=5w-2(w-3) | | 7y-4=216-2x | | 15-3.2x=-6.8 | | 8x+15=-57 | | (m+1.5)=1.5(2m+3) | | y=-x^2+8x-19 | | x+6(x-50)=750 | | 3y+2(y-5)=-1(3y-35)-y | | .55+q=.66 | | 5x-(2x+7)=2 | | -2(n+2)+6=16 | | .16x-.6=-.42 | | A-0.13=-.58 | | x+-4x=18 | | n+(n+2)=24-4(n+4) | | 16r-23=6r | | C=25000+40x+x^2 | | (7,4),(3,y)=.25 | | x+22=-10 | | 6x-22=5x+17+x | | 5x^2-9x-14=0 | | 99-92=38y-45y | | 3y-3x=5 | | -22-3e=-2e+e-3e | | 2(y-3)-2=2 | | 7(x+5)-2x-40=-3(2x-9.4)+4 | | 9(n+6)=10 |